Strategy Marketing Communications Department of Tourism and Cultural district of Jepara In Ascending The number of visitors Tirta Samudra Beach - Dwi Ratnasari, Yusniar; Setyabudi, S.Sos, MM, Djoko (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
The research is based on the phenomenon occurred, ie an increase in the number of tourists significantly in 2011 to 2014 to the area attractions Tirta Beach Samudra.Permasalahan this study is how the Strategic Marketing Communications Department of Tourism and Culture District of Jepara in Increasing Number of Visitors Tirta Samudra Beach , This study aims to determine the marketing communication strategy that used the Department of Tourism and Cultural district of Jepara in increasing the number of visitors Tirta Samudra Beach in Jepara. The method used in this research is descriptive qualitative case study method in the marketing communication strategy of Tourism and Culture to Tirta Samudra Beach. Data collection techniques used were interviews with research subjects and informants as well as documentation from the archives of the Department of Tourism and Cultural district of Jepara. Based on the results of research and discussion as well as using data analysis techniques using pairing pattern of the theory that predicted the pattern found in lapanganyaitu with the object of research is the communication strategy Department of Tourism and Cultural district of Jepara in increasing the number of visitors Turkish Tirta Samudra, it can be concluded that 1) Communicating program or a new thing in a variety of attractions as a form of publicity and promotion. 2) Establish communication with internal and external public. 3) Increase the events of Tourism and Cultural district of Jepara. 4) Promotion through media publications; internet, outdoor media, sales trip dll..5) Establish communication with mass media and the press in order to establish a good relationship.